2011
DOI: 10.1590/s1806-66902011000100013
|View full text |Cite
|
Sign up to set email alerts
|

Identification of cowpea genotypes for drought tolerance

Abstract: -The genotypes selection for drought tolerance is very important for world food production, principally in arid regions or sites with irregular rain distribution. The objective of this work was to identify cowpea genotypes with drought tolerance and water stress sensitivity characteristics. Two experiments were carried out with 20 treatments and four replications, one under water deficit during reproductive phase and another one under full irrigation. The water deficit was obtained applying half the water dept… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
36
1
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(56 citation statements)
references
References 7 publications
9
36
1
8
Order By: Relevance
“…Regarding the mass of 100 beans, mean values in cowpeas cultivated under full water supply were significantly higher than those in cowpeas exposed to water limiting conditions . Results from the present study confirmed that drought stress exerts a negative influence on cowpea productivity, as has been previously reported (Uarrota, 2010;Bastos et al, 2011;Nascimento et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Regarding the mass of 100 beans, mean values in cowpeas cultivated under full water supply were significantly higher than those in cowpeas exposed to water limiting conditions . Results from the present study confirmed that drought stress exerts a negative influence on cowpea productivity, as has been previously reported (Uarrota, 2010;Bastos et al, 2011;Nascimento et al, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Water stress interferes with several physiological plant processes. In the case of cowpea, other authors have observed significant reductions of physiological processes as a result of water stress, such as stomatal conductance and leaf water potential (MENDES et al, 2007;NASCIMENTO et al, 2011) as well as total chlorophyll content of leaves (BASTOS et al, 2011). As a consequence, the weight of the aerial parts is reduced.…”
Section: Resultsmentioning
confidence: 98%
“…Also, water stress at intervals of 15 to 20 days in the vegetative phase delayed the onset of flowering. Bastos et al (2011), studying the cultivar Tracuateua -192, found significant differences in the number of pods per plant, number of grains per pod, weight of 100 grains and productivity when subjected to moderate water stress in the reproductive phase. Figure 4 shows the LAI variability along the growth cycle in the three experimental years.…”
Section: Resultsmentioning
confidence: 99%
“…Entre os genótipos existe grande variabilidade quanto a essa característica de sobreviver em condições de deficiência hídrica. As principais mudanças que uma planta submetida ao estresse hídrico apresenta são: menor crescimento, redução da área foliar, maior crescimento do sistema radicular, enrolamento das folhas, redução de turgor, fechamento dos estômatos, abscisão floral e alteração na permeabilidade da cutícula (XOCONOSTLE-CAZARES et al, 2010;BASTOS et al, 2011;VARSHNEY et al, 2011;SILVA et al, 2011). Todas essas alterações citadas anteriormente limitam a produtividade, ocasionando danos ao produtor.…”
Section: Introductionunclassified